Connecting paths between juvenile and adult habitats in the Atlantic green turtle using genetics and satellite tracking. Issue 24 (11th December 2018) - Chambault, Philippine; de Thoisy, Benoît; Huguin, Maïlis; Martin, Jordan; Bonola, Marc; Etienne, Denis; Gresser, Julie; Hiélard, Gaëlle; Mailles, Julien; Védie, Fabien; Barnerias, Cyrille; Sutter, Emmanuel; et al.
Abstract: Although it is commonly assumed that female sea turtles always return to the beach they hatched, the pathways they use during the years preceding their first reproduction and their natal origins are most often unknown, as it is the case for juvenile green turtles found in Martinique waters in the Caribbean. Given the oceanic circulation of the Guiana current flowing toward Martinique and the presence of important nesting sites for this species in Suriname and French Guiana, we may assume that a large proportion of the juvenile green turtles found in Martinique are originating from the Suriname–French Guiana beaches. To confirm this hypothesis, we performed mixed stock analysis (MSA) on 40 green turtles sampled in Martinique Island and satellite tracked 31 juvenile green turtles tagged in Martinique to (a) assess their natal origin and (b) identify their destination. Our results from MSA confirm that these juveniles are descendant from females laying on several Caribbean and Atlantic beaches, mostly from Suriname and French Guiana, but also from more southern Brazilian beaches. These results were confirmed by the tracking data as the 10 turtles leaving Martinique headed across the Caribbean–Atlantic region in six different directions and 50% of these turtles reached the Brazilian foraging grounds used by the adult green turtles coming from French Guiana. One turtle left the French Guianan coast to perform the first transatlantic migration ever recorded in juvenile green turtles, swimming toward Guinea‐Bissau, which is the most important nesting site for green turtles along the African coast. The extensive movements of the migrant turtles evidenced the crossing of international waters and more than 25 exclusive economic zones, reinforcing the need for an international cooperative network to ensure the conservation of future breeders in this endangered species. Abstract : We satellite tracked 31 juvenile green turtles tagged in Martinique Island, and performed mixed stock analysis on 40 green turtles sampled at the same site to assess their natal origin. Our results from mixed stock analysis confirm that these juveniles are descendant from females laying on several Caribbean and Atlantic beaches, mostly from Suriname and French Guiana, but also from more South Brazil. These results were confirmed by the tracking data showing that 50% of the tracked turtles reached the Brazilian foraging grounds used by the adult green turtles coming from French Guiana.